Examining relationship between Palestine stock exchange and Amman stock exchange-cointegration approach - Abdul Hadi, Abdul Razak; Hamad, Shadi Ali; Yahya, Mohamed Hisham; Iqbal, Tahir (Canadian Center of Science and Education, 2013)
This paper aims at examining the probable equilibrium and dynamic relations between Palestine Stock Exchange (PEX) and Amman Stock Exchange (ASE). Within the framework of international trade theories, this study employs Engle-Granger Cointegration procedure (1987) as an estimation model involving monthly time series data from 1997 through 2011. The empirical results show that there is a significant equilibrium relationship between PEX and ASE, but fail to establish empirical evidence on dynamic relations between the two stock markets using Granger Causality tests. However, analysis of dynamic interactions during the post-sample period via Impulse-Response Functions and Variance Decomposition suggest that changes in ASE index do influence the performance of PEX.